Lessons in mathematical logic for high school students - Prepotente, Fe Lladoc (1972)
Specifically, the objective of this study was to construct lessons in mathematical logic for classes of academically talented high school students. Thus, it was considered a program of enrichment and a supplement to the secondary school mathematics curriculum. Lessons I to VI introduced the concepts of a sentence, negation, conjunction, disjunction, implication, and equivalence. Lessons VII to X dealt with the rules of inference and the last lesson introduced tautology. Because sets are often used in the lessons it is imperative that before any teaching of these lessons, both the students and the teacher must have a working knowledge of sets and its operations.